The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/anie.201403046
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of 3,3′‐Diaryloxindoles as Triarylmethanes with a Chiral All‐Carbon Quaternary Center: Phase‐Transfer‐Catalyzed SNAr Reaction

Abstract: Catalytic asymmetric synthesis of unsymmetrical triarylmethanes with a chiral all-carbon quaternary center was achieved by using a chiral bifunctional quaternary phosphonium bromide catalyst in the S(N)Ar reaction of 3-aryloxindoles under phase-transfer conditions. The presence of a urea moiety in the chiral phase-transfer catalyst was important for obtaining high enantioselectivity in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 101 publications
0
29
0
Order By: Relevance
“…After examining as eries of iron and coppers altsi tw as found that FeBr 3 was the most effective ( Table 1, entries [8][9][10][11][12]. Further studies revealed that varying the amount of FeBr 3 used had little effect on the product yields of 3a and the optimum results were obtained when the reactionw as conducted at 120 8C(Ta ble1,e ntry 7v ersus [13][14][15][16].…”
Section: Entrymentioning
confidence: 99%
“…After examining as eries of iron and coppers altsi tw as found that FeBr 3 was the most effective ( Table 1, entries [8][9][10][11][12]. Further studies revealed that varying the amount of FeBr 3 used had little effect on the product yields of 3a and the optimum results were obtained when the reactionw as conducted at 120 8C(Ta ble1,e ntry 7v ersus [13][14][15][16].…”
Section: Entrymentioning
confidence: 99%
“…Especially towards enantioselective alkylation reaction chiral phase transfer catalysts has am ajor control with variousnon-covalent interactions between the catalyst and the substrate helping in the enantioselectivity.F or the catalytic asymmetric synthesis of triarylmethanes bearing all carbon quaternary stereocenter,Shirakawa et al developed S N Ar reactiono fo xindoles with nitrofluoro benzenes under phase transferconditions to obtain 3,3'unsymmetrical diaryl oxindoles in high yields and enantioselectivities (up to 99 %y ield and 95 % ee)( Scheme 46). [79] Screening of various chiral bifunctionalb inaphthyl based phosphonium bromide phase transfer catalysts revealed catalyst( 32)p ossessing the urea moietyt ob et he optimal organocatalyst for this transformation.T he urea moiety formed hydrogen bondingi n-Scheme43. Mechanism of additiono fn ucleophile to and para-quinonemethides.…”
Section: Chiral Phase Transferc Atalysismentioning
confidence: 99%
“…We examined asymmetric S N Ar reaction of 3-phenyloxindole 24b and electron deficient aryl fluoride 76 under the influence of chiral bifunctional phosphonium bromides as phase-transfer catalysts (Scheme 13). 43 Although catalysts 68, 72a, and 72b possessing a hydroxy group or an amide group gave arylation product 77 in low to moderate enantioselectivities, the reaction with newlydesigned chiral bifunctional quaternary phosphonium bromide 72c possessing a urea moiety gave a product 77 in high yield and enantioselectivity. It is expected that the urea moiety of catalyst 72c interacts with nitroarene 76 through double hydrogen-bonding, giving rise to a well organized transition states that provides high stereocontrol.…”
Section: Scheme 12mentioning
confidence: 99%